Gingival fibromatosis with hypertrichosis syndrome: Case series of rare syndrome - Preetha Balaji; S M Balaji (Wolters Kluwer Medknow Publications, 2017)
Gingival fibromatosis with hypertrichosis syndrome is an extremely rare genetic condition characterized by profound overgrowth of hair and gums, as well as other variable features. Gingival fibromatosis is characterized by a large increase in the gingival dimension which extends above the dental crowns, covering them partially or completely. They were found to have a genetic origin, may also occur in isolation or be part of a syndrome, or acquired origin, due to specific drugs administered systemically. Congenital generalized hypertrichosis is a heterogeneous group of diseases with continuing excessive growth of terminal hair without androgenic stimulation. It has informally been called werewolf syndrome because the appearance is similar to that of a werewolf. Various syndromes have been associated with these features such as epilepsy, mental retardation, cardiomegaly, or osteochondrodysplasia. As so far very few cases have been reported in literature, we are reporting a series of three cases with management of the same. The excess gingival tissues, in these cases, were removed by conventional gingivectomy under general anesthesia. The postoperative result was uneventful and the patient's appearance improved significantly. Good esthetic result was achieved to allow patient to practice oral hygiene measures. Though this is not a serious condition clinically, psychosocial trauma cannot be neglected owing to the cosmetic disfigurement it produces.